Titanium(IV) Isopropoxide as an Efficient Catalyst for Direct Amidation of Nonactivated Carboxylic Acids - Lundberg, Helena; Tinnis, Fredrik; Adolfsson, Hans (Synlett, 2012)
Secondary and tertiary amides are formed in high yields, in an efficient and environmentally benign titanium(IV) isopropoxide catalyzed direct amidation of carboxylic acids with primary and secondary amines.
Keywords: amides; titanium; catalysis; carboxylic acids; amines